Geopolitical Contestation and Spatial Strategies in the Iran–Israel Rivalry: Regional and Global Implications - Kaslam, Kaslam; Emynorane, Ralaivao Hanginiaina (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2026)
This study investigates the evolving geopolitical rivalry between Iran and Israel by analyzing the interdependent roles of spatial strategy, proxy warfare, and alliance formation. It aims to explain how geography, military networks, and ideological narratives coalesce to sustain conflict in the Middle East. Employing a qualitative case study approach, the research integrates narrative analysis, geospatial mapping, and documentary interpretation. Data sources include government statements, satellite imagery, open-source intelligence, and scholarly literature. The findings reveal that Iran’s strategic behavior is rooted in its access to key maritime chokepoints, its support for territorially embedded proxies, and its multi-vector alliances with global powers. Israel counters through infrastructural control in the Eastern Mediterranean, forward military doctrine, and regional normalization agreements. The analysis further uncovers how both states utilize spatialized narratives to legitimize their actions and project deterrence. Additionally, cyber operations emerge as a non-territorial extension of conflict, enabling both actors to influence adversaries without confrontation. This research contributes new theoretical and methodological perspectives by integrating physical and discursive geographies into a unified explanatory model. The study provides a scalable framework for analyzing hybrid conflicts and offers strategic insights relevant to regional diplomacy, defense planning, and security governance.